Penerapan Strategi Pembelajaran untuk Meningkatkan Kemampuan Berpikir Siswa pada Materi Akhlak Mulia (Kejujuran) dalam Mata Pelajaran Akidah Akhlak di SD An Namiroh 4 Pekanbaru - Rinah; Bainar (JURNAL ARMADA PENDIDIKAN, 2026)
This research is motivated by students' low critical thinking skills in the teaching of Aqidah Akhlak (Aqidah Akhlak) on honesty, which is still dominated by conventional methods. The purpose of this study is to improve students' critical thinking skills through the application of Higher Order Thinking Skills (HOTS)-based learning strategies. The study used Classroom Action Research (CAR) with a quantitative approach, implemented in two cycles, including planning, implementation, observation, and reflection. The population and sample were students at An Namiroh 4 Elementary School, Pekanbaru. Data collection techniques used tests, observation, and documentation, while data analysis was conducted using descriptive quantitative and qualitative methods. The results showed an increase in students' critical thinking skills, indicated by an increase in the average score from 60 with 40% completion in the pre-cycle to 70 with 65% completion in the first cycle and an increase to 82 with 90% completion in the second cycle. Improvements were also seen in students' more active, confident activities, and their ability to analyze and evaluate problems. This research recommends the continued use of HOTS strategies in teaching Aqidah Akhlak and other subjects to enhance critical thinking skills and develop students' character.